Carbon Dioxide Sequestration in Subsurface Formations to Enhance Hydrocarbon Recovery: Field Case Study from Southern Iraq - Kadhim, Mahdi M.; Abdul Hussein, Hassan A.; Abdulridha, Hayder L. (Journal of Petroleum Research and Studies, 2025)
Concern about reducing greenhouse gas emissions particularly those of carbon dioxide has developed along with an understanding of global warming and climate change and joined with enhanced oil recovery. Thus, research on improved oil recovery and supporting reservoir pressure utilizing greenhouse gases has been conducted throughout the last few decades. The current study focuses on achieving the oil production target from the X oil field. It is located in southern Iraq; this field is thought to be the Y formation; planned by National Oil Company with CO2 miscible gas injection and test the possibility of applied sequestration of CO2 in the aquifer as reduced emission project. Building a 3D dynamic model with CMG-2018 based on a geological model exported from Petrel employed to investigate distinct developing plans with varying operational constraints. The compositional simulator (GEM-2018) is used to model Y formation. The model was calibrated with W-4 well testing because of a lack of production data. The production case scenario has been suggested to develop Y formation as the preferred case based on the height recovery factor. The best case is the five-spot CO2 injection with a plateau of 30 Kbbl/d for twenty years with production above the bubble point and with stored CO2 of 5.75 MMTon in the S21 and exploiting the three abandoned to stored CO2 of 3.265 MMTon in the aquifer as soluble emission gas.